2005
DOI: 10.1016/j.jcf.2005.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole therapy in children with cystic fibrosis

Abstract: Voriconazole may be a useful adjunctive therapy for ABPA in CF. Voriconazole monotherapy appears to be an alternative treatment strategy when oral corticosteroids may not be suitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
71
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 22 publications
0
71
0
1
Order By: Relevance
“…On the other hand, voriconazole-related photosensitivity has rarely been reported in CF children or adult patients [2,[6][7]. This high rate of photosensitivity was not in line with the previous reported ratio of 14% in CF children [2], but closer to 40% in lung-transplanted CF adults [6]. A recent Canadian case report raised the question of voriconazole safety as five out of the six CF children treated with voriconazole presented photosensitivity.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…On the other hand, voriconazole-related photosensitivity has rarely been reported in CF children or adult patients [2,[6][7]. This high rate of photosensitivity was not in line with the previous reported ratio of 14% in CF children [2], but closer to 40% in lung-transplanted CF adults [6]. A recent Canadian case report raised the question of voriconazole safety as five out of the six CF children treated with voriconazole presented photosensitivity.…”
mentioning
confidence: 76%
“…Voriconazole, a new triazole antifungal, has been recognised as efficient and safe in the treatment of invasive aspergillosis [1][2]. Since it is available orally, voriconazole became the first alternative to itraconazole.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…52 Kolve and others 53 studied 37 immunocompromised pediatric patients with invasive fungal infections and found that 86% of the patients with probable or proven infections and 100% of those with possible infections had a response to treatment and their condition remained stable. In a case series involving patients with cystic fibrosis and recurrent allergic bronchopulmonary aspergillosis, Hilliard and others 54 reported a response to voriconazole therapy.…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…[50][51][52][53][54] In one study, treatment success (as determined by clinical, radiographic, and mycological evidence) was 45% among 58 children (ranging in age from 9 months to 15 years) with aspergillosis, candidiasis, or scedosporiosis. 50 Cesaro and others 51,52 conducted 2 small observational studies in pediatric patients with invasive fungal infections.…”
Section: Pediatric Patientsmentioning
confidence: 99%